Pneumocystis jirovecii in Spanish Patients With Heart Failure - Merino-Casallo, Izarbe; Friaza, Vicente; Menao, Sebastián; Domingo, José María; Olivera, Susana; Calderón, Enrique J.; Torralba, Miguel Ángel (Frontiers in Public Health, 2019)
Objective:Pneumocystis colonization is frequent in patients with chronic obstructive pulmonary disease (COPD) producing local and systemic inflammation. Heart failure is also a common comorbidity among patients with COPD. Heart failure is a chronic, frequent, and disabling condition with high morbidity and mortality, but with a modifiable course where endothelial dysfunction and pulmonary arterial hypertension have great importance. Animal models have shown that Pneumocystis infection can cause relevant functionally changes in vascular responses in the lung, promoting the development of pulmonary hypertension. Pneumocystis colonization could be a hidden cause of worsening heart failure through it capacity to induce inflammatory response with subsequent endothelial dysfunction and pulmonary hypertension. The aim of the present study was to investigate the prevalence of Pneumocystis jirovecii colonization in heart failure patients and its possible association with reduced or preserved ejection fraction. Methods: A cross-sectional study was carried out including 36 heart failure patients and 36 control cases. Identification of P. jirovecii colonization was performed by means of molecular techniques in oropharyngeal washing. Results:Pneumocystis-DNA was identified in oropharyngeal washing in 1 (2.7%) of 36 heart failure patients and in 3 (8.3%) of 36 controls. Conclusions:Pneumocystis colonization does not seem to have a role in the pathophysiology of heart failure.